The Effectiveness of Azolla pinnata in Inhibiting the Growth of Salmonella typhi - Evy Ratnasari Ekawati; M. Sungging Pradana (Biota, 2019)
Human digestive tract infections can be caused by viruses, bacteria, and protozoa. Bacterial resistance to antibiotics can frustrate therapy with antibiotics. Today many researchers develop herbal medicines from plants for microbial infections. The benefits of medicinal plants depend on several components of chemicals that can have an influence on the human body. One of the plants that can be used is Azolla. Azolla has many nutrients and phytochemical compounds such as flavonoid, tannin, and saponin which have antimicrobial activity. This study used dried Azolla extract which was divided into several doses, namely 20%, 40%, 60%, 80% and 100% b/v. Azolla extract activity test was carried out by observing the presence of inhibition zones formed after incubation. Azolla extract test results obtained all doses in the resistance category with a diameter of no more than 10 mm. One way Anova test obtained a significance value of 0.000<α = 0.05, which means that there is a difference between the administration of Azolla pinnata extract dose to its ability to inhibit the growth of Salmonella typhii. Duncan test showed that the treatment of Azolla pinnata 60%, 80% and 100% of Salmonella typhii showed results that were not significantly different. The results of the study concluded that Azolla extract can be used to inhibit the growth of Salmonella typhii bacteria so that it can be developed into traditional medicine.